The abrupt temperature changes in the plantar skin thermogram of the diabetic patient: looking in to prevent the insidious ulcers. Issue 1 (1st January 2018) - Renero-C, Francisco-J
ABSTRACT: Background: One of the complications of the diabetes mellitus is the amputation of the lower limbs. This complication may be developed after an insidious ulcer, that may be raised by the peripheral neuropathy or the ischaemic limb, and that the ulcer get infected. That is, to develop an ulcer, in the diabetic patient, three factors should be taken into the account, the autonomic nervous system, the blood supply and the inmune system.Methods: In this work, the thermogram is used to identify regions on the plantar skin with blood supply deficiencies and the behaviour of the thermoregulation process. Within the thermogram of the plantar skin, it can be identify local regions with low and high temperatures that corresponds to ischemic or inflammatory process on that part of the skin.Results: The findings within the 186 thermograms of diabetic patients, obtained from three hospitals and from INAOE facilities, showed, first, the thermograms of the plantar skin of two diabetic patients, acquired in two different times show that the temperature distribution and the average temperatures, vary slightly for a period of weeks. Second, the thermograms of two patients, who both developed insidious ulcers which evolved favourable, demonstrated the importance of the immune system and the drug therapy. These patients are, one who has a Charcot foot, and in the second one, the patient had loss the sensibility of the feet. Finally, the thermograms of two patients, showing abrupt temperature change within small regions in the plantar skin, are discussed.Conclusion: A diabetic patient, with an asymmetric thermogram, as physiological interpretation of the thermoregulation, may indicate a decrease of the blood supply, which may be corroborated by vascular ultrasound. The regions of abrupt temperature change, cold or hot spots, may correspond to ischaemic or inflammatory processes.